G protein Galphai functions immediately downstream of Smoothened in Hedgehog signalling. - Ogden, S.K.; Fei, D.L.; Schilling, N.S.; Ahmed, Y.F.; Hwa, J.; Robbins, D.J. (Nature, 2008)
The hedgehog (Hh) signalling pathway has an evolutionarily conserved role in patterning fields of cells during metazoan development, and is inappropriately activated in cancer. Hh pathway activity is absolutely dependent on signalling by the seven-transmembrane protein smoothened (Smo), which is regulated by the Hh receptor patched (Ptc). Smo signals to an intracellular multi-protein complex containing the Kinesin related protein Costal2 (Cos2), the protein kinase Fused (Fu) and the transcription factor Cubitus interruptus (Ci). In the absence of Hh, this complex regulates the cleavage of full-length Ci to a truncated repressor protein, Ci75, in a process that is dependent on the proteasome and priming phosphorylations by Protein kinase A (PKA). Binding of Hh to Ptc blocks Ptc-mediated Smo inhibition, allowing Smo to signal to the intracellular components to attenuate Ci cleavage. Because of its homology with the Frizzled family of G-protein-coupled receptors (GPCR), a likely candidate for an immediate Smo effector would be a heterotrimeric G protein. However, the role that G proteins may have in Hh signal transduction is unclear and quite controversial, which has led to widespread speculation that Smo signals through a variety of novel G-protein-independent mechanisms. Here we present in vitro and in vivo evidence in Drosophila that Smo activates a G protein to modulate intracellular cyclic AMP levels in response to Hh. Our results demonstrate that Smo functions as a canonical GPCR, which signals through Galphai to regulate Hh pathway activation.